1989
DOI: 10.1088/0953-8984/1/6/002
|View full text |Cite
|
Sign up to set email alerts
|

A superstructure in single-crystal YBa2Cu3O7-δ

Abstract: A new form of superstructure with a a X 2 V 5 x 1 supercell oriented at 45" to the original unit-cell axes has been found in a YBa2Cu30,_, single crystal by means of electron diffraction and electron microscopy. It is suggested that this superstructure results from a substructure modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Finally, the introduction of Hf and Zr impurities leads to substitutional impurities, which contribute to the formation of additional pinning centers. These (due to the low coherence length in this HTSC) may also be sufficiently effective on point defects, including oxygen vacancies [21,22] and impurities [5,23]. Here, we investigate the influence of Hf impurities on the magnetoresistive characteristics of YBa 2 Cu 3 O 7−δ ceramics in the transition interval to the superconducting state.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the introduction of Hf and Zr impurities leads to substitutional impurities, which contribute to the formation of additional pinning centers. These (due to the low coherence length in this HTSC) may also be sufficiently effective on point defects, including oxygen vacancies [21,22] and impurities [5,23]. Here, we investigate the influence of Hf impurities on the magnetoresistive characteristics of YBa 2 Cu 3 O 7−δ ceramics in the transition interval to the superconducting state.…”
Section: Introductionmentioning
confidence: 99%
“…Structural defects in the compounds of the 1-2-3 system. In pure YBa2Cu3O7-δ single crystals, depending on the oxygen deficiency and the synthesis technology, the following structural defects are observed: point defects such as oxygen vacancies that form in the CuO2 planes, planar defects of the (001) type, twin boundaries, dislocations, and the so-called 2√2x2 √2 structures [20] observed at oxygen deficiency δ = 6.8 -6.9.…”
mentioning
confidence: 99%
“…Plane defects are twinning planes, which are formed during the "tetra-ortho" transition and minimize the elastic energy of the crystal. Twin boundaries are planes with a tetragonal structure as a result of the presence of layers containing oxygen vacancies located along the twin boundary [20,21]. Electron microscopic studies have shown [18,19,21] that at the initial stage of the tetra-ortho transition, domain nuclei are formed, in which two families of coherent interfaces (110) and (110) are formed.…”
mentioning
confidence: 99%